Development of a General Time-Dependent Model for Geogrids. Issue 4 (2002) - Kaliakin, V.N.; Dechasakulsom, M.
Abstract : A simple yet general time-dependent mathematical model for geogrid reinforcement is presented. The model is based on the assumption that the time-dependent behavior of the reinforcement can be represented by creep isochrones. The model is capable of simulating the general time-dependent response of geogrids subjected to monotonic loading, which includes creep and relaxation as special cases. The model is formulated, calibrated, implemented, and its predictive capabilities verified. The range of applicability and limitations of the model are noted.